Evaluation of stability of aqueous dispersions using zeta potential data - Pompeu, Lenise Deon; Pinton, Andriéle Pinheiro; Finger, Marcel Goulart; Cadó, Ronan Gorski; Severo, Vinicius de Avila; Pinheiro, Lailla; Bulhões, Luis Otavio (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Surface properties of nanomaterials through the determination of the zeta potential (ZP) are important characteristics influencing the dispersion stability. Water was used as a dispersant and cetyltrimethylammonium bromide (CTAB) was adsorbed on nanoparticles. The ZP was obtained using the electrophoretic light scattering method. Magnitude and the sign of zeta potential of various metal oxide nanoparticles (NPs), active carbon and hydroxyapatite dispersed in water depend highly of the compound and environment. For example, in the case of naked TiO2 at pH 7, the zeta potential increased from -12.7 to 8.2 mV for AgTiO2. Most oxides and hydroxyapatite aqueous dispersions exhibit high stability. Stability in all investigated systems is mostly influenced by pH. In addition, measurements of the zeta potential at different pHs allow prediction of the macroscopic behavior of the dispersions.